Learn and Practice Homeopathy Exactly and Accurately - Krishnaamurthy, V. (Homœopathic Links, 2015)
Theory is good and necessary, but he who puts theory into practice, lives in, with and for the student. The value of the exact phrase and the right repertory: Kent, Boericke, Lilianthal, Knerr, Yingling, Hering.
Keywords: Lycopodium clavatum; Gossypium; Arnica montana; Cicuta virosa; Phosphorus; Hypericum perforatum; Achillea; Millefolium; Cantharis; Carbolicum acidum; Cimex lectularius; Pulsatilla nigricans; Opium; Belladonna; Ignatia amara; Crotalus horridus